Shampoo containing lauryl glycoside cross-linked polymer salt as well as preparation method and application of shampoo

By incorporating lauryl glycoside crosspolymer salt and AES into the shampoo, the problems of excessive irritation and insufficient viscosity in existing shampoos have been solved, achieving a gentler and more viscous shampooing effect and improving the consumer experience.

CN121370664APending Publication Date: 2026-01-23LAFANG CHINA CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511971986.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-25
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

The anionic surfactant sodium lauryl ether sulfate (AES) in existing shampoos is highly irritating, while the nonionic surfactant alkyl glycosides, although mild, do not have a thickening effect, making it difficult to meet consumer demands for both mildness and viscosity.

Method used

By introducing lauryl glycoside crosspolymer salt and AES, a shampoo formula containing lauryl glycoside crosspolymer salt is formed. Through the synergistic effect of lauryl glycoside crosspolymer salt and other ingredients, the viscosity and gentleness of the system are improved.

Benefits of technology

It significantly reduces the irritation of the AES system, increases viscosity, and improves hair combing performance, enhancing the user experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the field of macromolecular surfactants, and particularly relates to a lauryl glycoside cross-linked polymer salt shampoo which comprises sodium laureth sulfate, cocamidopropyl betaine and lauryl glycoside cross-linked polymer salt. The mass fraction of the lauryl glucoside cross-linked polymer salt is 1%-10%; the mass fraction of the sodium laureth sulfate is 9.3%-17.8%; the mass fraction of the cocamidopropyl betaine is 5%-8%; furthermore, the shampoo containing the lauryl glucoside cross-linked polymer salt also comprises decyl glucoside. The lauryl glycoside cross-linked polymer salt is adopted to reduce the irritation of an AES + cocamidopropyl betaine system, and the viscosity of the system can be remarkably improved. In a shampoo system containing AES, cocamidopropyl betaine and decyl glucoside, the viscosity of the system is also remarkably improved by introducing the lauryl glucoside cross-linked polymer salt. The shampoo containing the lauryl glycoside cross-linked polymer salt can improve the combing performance of hair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymeric surfactants, specifically relating to a shampoo containing lauryl glycoside cross-linked polymer salt, its preparation method, and its application. Background Technology

[0002] Since hair care products come into direct contact with the scalp, gentleness and safety are the performance indicators that consumers care about most. The main ingredient in shampoo is surfactant, and the gentleness of the surfactant has the greatest impact on the overall gentleness. It is generally believed that anionic surfactants are more irritating than nonionic surfactants. Sodium lauryl ether sulfate (AES) is the most commonly used surfactant in shampoos, but it also has its own irritants. Improving the overall gentleness by compounding it with other surfactants is one effective method.

[0003] Nonionic surfactants, specifically alkyl glycosides, are currently widely used mild surfactants in shampoos. They can be used in AES systems to reduce overall irritation, but they do not have the advantages of anionic surfactants such as sodium lauryl ether sulfate, which are easy to thicken. Summary of the Invention

[0004] To address the aforementioned issues, this invention utilizes a surfactant, lauryl glycoside crosspolymer salt, which can be compounded with AES to reduce system irritation and improve mildness. This surfactant is introduced into AES-based shampoo formulations to enhance the overall mildness of the shampoo. Simultaneously, as an anionic surfactant, the lauryl glycoside crosspolymer salt can also increase the viscosity of the shampoo system, thereby improving overall performance by enhancing formulation stability, consumer control during use, and overall user experience.

[0005] To solve the above-mentioned technical problems, the present invention adopts the following technical solution: This invention provides a shampoo containing lauryl glycoside crosspolymer salt, comprising sodium laureth sulfate, cocamidopropyl betaine, and lauryl glycoside crosspolymer salt; the chemical formula of the lauryl glycoside crosspolymer salt is as follows:

[0006] Where n = 1 to 3, and R is CH3(CH2). 11 -

[0007] Furthermore, the mass fraction of the lauryl glycoside crosspolymer salt is 1% to 10%; the purity of the lauryl glycoside crosspolymer salt is 55% to 65%.

[0008] Furthermore, the sodium lauryl ether sulfate has a mass fraction of 9.3%–17.8%; and the cocamidopropyl betaine has a mass fraction of 5%–8%. The purity of the sodium lauryl ether sulfate is 70%; the purity of the cocamidopropyl betaine is 45%.

[0009] Furthermore, the sodium lauryl ether sulfate has a mass fraction of 12.3% to 17.8%; the cocamidopropyl betaine has a mass fraction of 5% to 8%; and the lauryl glycoside crosspolymer salt has a mass fraction of 1% to 7%.

[0010] Furthermore, the shampoo containing lauryl glycoside crosspolymer salt also includes: cationic guar gum, silicone emulsion, cocamide MEA, hydrogenated castor oil, ethylene glycol distearate, phenoxyethanol, sodium benzoate, citric acid, sodium chloride, and water.

[0011] Furthermore, the shampoo containing lauryl glycoside crosspolymer salt comprises the following components in the indicated mass fractions: The lauryl glycoside cross-linked polymer salt is 1%–10%. The sodium lauryl ether sulfate content is 9.3%–17.8%. The cocamidopropyl betaine is 5%–8%. The cationic guar gum is 0.2% to 0.5%. The silicone emulsion is 1.5% to 3%. The cocoamide MEA content is 0.8%–10%. The hydrogenated castor oil is 0.2% to 0.3%. The ethylene glycol distearate is 0.8% to 1.0%. The phenoxyethanol content is 0.7% to 0.8%. The sodium benzoate is 0.2% to 0.3%. The citric acid content is 0.04% to 0.1%. The sodium chloride is 1.0%. Water balance.

[0012] Furthermore, the shampoo containing lauryl glycoside crosspolymer salt also includes decyl glucoside; the mass fraction of decyl glucoside is 2.5% to 5%; and the purity of decyl glucoside is 55% to 65%.

[0013] Accordingly, the present invention also provides a method for preparing the shampoo containing lauryl glycoside crosspolymer salt, comprising the following steps: S1. The citric acid, sodium lauryl ether sulfate, cocamidopropyl betaine, and lauryl glycoside crosspolymer salt are added to the water and mixed to obtain intermediate product x; S2. Add the cocoamide MEA, the hydrogenated castor oil, and the ethylene glycol distearate to the intermediate product x, and mix to obtain the intermediate product y; S3. Add the cationic guar gum to the intermediate product y and mix to obtain the intermediate product z; S4. Cool the intermediate product z, add the silicone emulsion, phenoxyethanol, sodium benzoate, and sodium chloride, mix, and obtain the shampoo containing lauryl glycoside crosspolymer salt.

[0014] Furthermore, the present invention also provides a method for preparing the shampoo containing lauryl glycoside crosspolymer salt, comprising the following steps: S1. The citric acid, sodium lauryl ether sulfate, cocamidopropyl betaine, lauryl glycoside crosspolymer salt, and decyl glucoside are added to the water and mixed to obtain intermediate product x; S2. Add the cocoamide MEA, the hydrogenated castor oil, and the ethylene glycol distearate to the intermediate product x, and mix to obtain the intermediate product y; S3. Add the cationic guar gum to the intermediate product y and mix to obtain the intermediate product z; S4. Cool the intermediate product z, add the silicone emulsion, phenoxyethanol, sodium benzoate, and sodium chloride, mix, and obtain the shampoo containing lauryl glycoside crosspolymer salt.

[0015] Furthermore, in steps S1, S2, and S3, the mixing method independently includes stirring, and the degree of mixing includes complete dissolution; In step S4, the mixing method includes stirring, and the degree of mixing includes complete dissolution and dispersion. In step S1, the mixing temperature is 80°C; in step S4, the cooling temperature is 48°C.

[0016] Accordingly, the present invention also provides an application of the shampoo containing lauryl glycoside crosspolymer salt to increase the viscosity of the shampoo.

[0017] The lauryl glycoside crosspolymer salt is specifically sodium lauryl glucoside crosspolymer sulfonate.

[0018] Compared with the prior art, implementing the present invention has the following beneficial effects: 1. The present invention uses lauryl glycoside cross-linked polymer salt, which not only reduces the irritation of the shampoo system with AES as the main surfactant, but also significantly improves the viscosity of the AES + cocamidopropyl betaine system. In contrast, if commonly used surfactants are used, whether it is the anionic surfactant sodium cocoamphoacetate or the nonionic surfactant decyl glucoside, neither has the function of significantly improving the viscosity performance of this system.

[0019] 2. The lauryl glycoside cross-linked polymer salt not only has a synergistic thickening effect on the AES + cocamidopropyl betaine shampoo system, but also significantly increases the viscosity of the AES + cocamidopropyl betaine + decyl glucoside shampoo system.

[0020] 3. The shampoo of the present invention can also improve the hair combing performance of the system. It is speculated that this is because the lauryl glycoside cross-linked polymer salt and other components in the system work synergistically to help improve the deposition of conditioning agents such as silicone oil on the hair, thereby improving dry and wet combing performance. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.

[0022] I. Raw material information for each embodiment and comparative example: Sodium lauryl ether sulfate: active ingredient content (i.e. purity) is 70%; Cocamidopropyl betaine: active ingredient content is 45% by mass; Lauryl glycoside cross-linked polymer salt: active ingredient content is 55-65%, brand name Runmild® HLC, chemical structure formula is shown below, where n=1~3, R is CH3(CH2). 11 -; Decyl glucoside: active ingredient content is 55-65%, brand name is APG2000; Sodium lauroamphoacetate: active ingredient content is 25-29%, brand name is Dehyton® ML; Cationic guar gum: brand name N-HANCE 3197; Silicone oil emulsion: a commercially available silicone emulsion, brand name BELSIL® LAF 6136 E; Low-viscosity silicone oil nanoemulsion: a self-made organosilicon emulsion (1000cst silicone oil, particle size 283nm); Sodium methyl cocoyl taurate: active ingredient content is 25-30% by mass; PQ10 (Polyquaternium-10): Tianci, POLYQUTA 3000; Cocamide MEA, ethylene glycol distearate, phenoxyethanol, sodium benzoate, citric acid, and sodium chloride: all contain 100% active ingredients.

[0023] The raw materials with an "active ingredient content" of less than 100% contain not only "active ingredients" (the corresponding target compounds) but also water and other components.

[0024]

[0025] II. Shampoo preparation methods for each embodiment and comparative example: The specific raw materials and their contents for each embodiment and comparative example are shown in Table 1 and Table 2.

[0026] The specific preparation steps of the embodiment are as follows: (1) Add citric acid, sodium lauryl ether sulfate, cocamidopropyl betaine, lauryl glycoside crosspolymer salt and decyl glucoside (if present) to deionized water and stir at 80°C until fully dissolved; (2) Add cocamide MEA, hydrogenated castor oil, and ethylene glycol distearate, and stir until fully dissolved; (3) Add cationic guar gum and stir until fully dissolved; (4) Cool down to 48°C, add organosilicon emulsion (silicone oil emulsion or low-viscosity silicone oil nanoemulsion), phenoxyethanol, sodium benzoate and sodium chloride, stir to dissolve and disperse fully to obtain shampoo.

[0027] The specific preparation steps of the comparative example differ from those of the examples in that sodium methyl cocoyl taurate and sodium lauroyl amphoteric acetate are added together with the raw materials in step (1) of the above examples; and polysiloxane quaternary ammonium salt-16, PO and other components are added together with the raw materials in step (4) of the above examples.

[0028] III. Viscosity Test: Test procedure: Turn on the rheometer air compressor, thermostat, and other hardware and software in sequence, set the temperature, select CP60-1, place the sample, lower the measuring head to the test position, and obtain the viscosity (unit: mPa·s).

[0029] The viscosity test results of each embodiment and comparative example are shown in Table 1 and Table 2.

[0030] IV. Zein Stimulation Test: Test procedure: Take the sample to be tested and prepare a 10% aqueous solution; take 30 mL of the prepared solution, add 1~3 g of zein reagent, stir thoroughly at 25℃, and filter to remove excess zein protein; use a Kjeldahl nitrogen analyzer to determine the mass fraction of nitrogen Za in the filtrate; take another appropriate amount of the prepared solution without zein, and use a Kjeldahl nitrogen analyzer to determine the mass fraction of nitrogen Zb in the solution. Zein value (unit: gN / L) = Za – Zb.

[0031] The Zein value test results for each embodiment and comparative example are shown in Table 1 and Table 2.

[0032] Table 1. Formulations and viscosity and irritation test results of shampoos from Examples 1-9 and Comparative Example 1

[0033] Table 2. Formulations and viscosity and irritation test results of shampoos from Examples 10-11 and Comparative Examples 2-9

[0034] (Note: There are differences in the total amount of surfactant added among the examples and comparative examples in Tables 1 and 2. The purpose is to keep the content of the target component of the surfactant at the same level.) The test results in Tables 1 and 2 show that: (1) The viscosities of Examples 1-5 were 9622, 9731, 12511, 15604 and 5500 mpa.s, respectively, which all meet the general usage requirements of shampoo. It can be seen that as the amount of lauryl glycoside cross-linked polymer salt added increases (1% to 7%), the viscosity of the AES + cocamidopropyl betaine surfactant system gradually increases significantly while the AES content gradually decreases (17.8% to 9.3%). The thickening effect of the system is best when the amount of lauryl glycoside cross-linked polymer salt added reaches 7%. However, when the amount of lauryl glycoside cross-linked polymer salt added is 10% (Example 5), the viscosity of the system rapidly decreases to 5500 mpa.s.

[0035] The viscosities of Comparative Examples 2 and 5 were 8521 and 9142 mPa·s, respectively. This demonstrates that the addition of lauryl glycoside crosspolymer salt significantly increased the viscosity of the AES + cocamidopropyl betaine surfactant system, even with only 1% added as in Example 1. Similarly, in Comparative Example 5, although the sodium chloride addition was 1.225%, higher than in Examples 1-4, theoretically higher sodium chloride would be more beneficial for increasing system viscosity. However, Comparative Example 5 did not add lauryl glycoside crosspolymer salt, and its actual system viscosity was still lower than in Examples 1-4. On the other hand, although the viscosity of Comparative Example 5 was higher than that of Example 5, Example 5, with only 1.0% sodium chloride added, also achieved a system viscosity exceeding 5000 mPa·s, meeting the general usage requirements of shampoo, further illustrating the thickening effect of lauryl glycoside crosspolymer salt on the AES + cocamidopropyl betaine surfactant system.

[0036] (2) The Zein values ​​of Examples 1-5 were 2.68, 2.43, 2.04, 1.78 and 1.24 gN / L, respectively. The smaller the Zein value, the better the system's mildness. It can be seen that as the amount of lauryl glycoside cross-linked polymer salt added increases, the irritation of the AES+cocamidopropyl betaine surfactant system gradually decreases. When the amount added is 7% and 10%, the system exhibits no irritation.

[0037] The Zein values ​​of Comparative Examples 2 and 5 were 2.77 and 2.67 gN / L, respectively, both higher than those of Examples 1-5, indicating greater irritation. Among them, Comparative Example 2 had the same AES content as Example 1, and Comparative Example 5 had the same AES content as Example 3. However, compared with Comparative Examples 2 and 5, Examples 1 and 3 added 1% and 3% lauryl glycoside crosspolymer salt, respectively, resulting in a decrease in the Zein value of the system. This further demonstrates that the addition of lauryl glycoside crosspolymer salt significantly reduces the irritation of the AES + cocamidopropyl betaine surfactant system.

[0038] (3) The viscosities of Example 3, Comparative Example 3 and Comparative Example 4 were 12511, 6391 and 7442 mpa.s, respectively. However, the contents of lauryl glycoside cross-linked polymer salt, decyl glucoside and sodium lauroyl amphoteric acetate active ingredients were similar in the three groups of experiments. It is speculated that the reason for the difference in viscosity is that lauryl glycoside cross-linked polymer salt was introduced into the AES+cocamidopropyl betaine surfactant system, which significantly increased the viscosity of the system. The viscosity was nearly twice that of the system with the introduction of decyl glucoside or sodium lauroyl amphoteric acetate.

[0039] (4) The viscosities of Example 10 and Comparative Example 6 were 10341 and 8315 mpa.s, respectively. It can be seen that the addition of 2.5% lauryl glycoside cross-linked polymer salt raw material has a thickening effect on the AES + cocamidopropyl betaine + decyl glucoside surfactant system.

[0040] Generally, with the same sodium chloride content, theoretically, the greater the amount of AES added, the greater the viscosity of the system. However, the amount of AES added in Comparative Example 8 was greater than that in Example 11. The viscosity of Example 11 (11256 mPa·s) was actually higher than that of Comparative Example 8 (7586 mPa·s). This shows that adding 5% lauryl glycoside cross-linked polymer salt raw material has a thickening effect on the AES + cocamidopropyl betaine + decyl glucoside surfactant system.

[0041] Comparative Examples 7 and 8 had higher decyl glucoside content than Comparative Example 6, but lower viscosity. This shows that in the AES + cocamidopropyl betaine surfactant system, the introduction of decyl glucoside alone, regardless of the amount added, does not have the thickening effect of introducing lauryl glycoside cross-linked polymer salt.

[0042] (5) The main surfactant in Comparative Example 1 was sodium methyl cocoyl taurate (active content 25-30%, usage in shampoo 34.0%), and the main surfactant in Example 3 was AES (active content 70%, usage in shampoo 13.6%). The target component content of the main surfactants in both examples was basically the same, but the viscosity of the product in Comparative Example 1 was less than 300 mPa·s, which was much lower than the 12511 mPa·s in Example 3. It can be seen that the effect of lauryl glycoside cross-linked polymer salt on viscosity in different surfactant systems is very significant. In the shampoo system of the present invention, AES, cocamidopropyl betaine and lauryl glycoside cross-linked polymer salt have a synergistic thickening effect.

[0043] (6) The viscosity of Comparative Example 9 was 3669 mPa·s, which was significantly lower than that of Example 1 (9622 mPa·s), further demonstrating that there was a synergistic thickening effect among the surfactants in the shampoo system of the present invention. It can be seen that the viscosity-regulating effect of lauryl glycoside crosslinked polymer salt in the Comparative Example 9 system was not obvious, but it could play a synergistic role in the formulation system of the present invention.

[0044] Example of results (performance testing) Shampoo samples from some of the embodiments and comparative examples were used as samples for hair combing performance testing. Each group of samples was tested with wet hair and dry hair. The test items included combing force and tangling force.

[0045] The basic testing steps are as follows: 1) Select clean and similar healthy hair bundles, and ensure that the hair bundles are equilibrated in a constant temperature and humidity chamber for a certain period of time; 2) Apply standard cleaning solution evenly to both sides of the hair strand to clean and remove excess water. Keep the hair moist and perform a baseline wet hair combing test. Place the hair in a constant temperature and humidity chamber to dry and then perform a baseline dry hair combing test. 3) After the hair strands are evenly coated with the sample and washed to remove excess water, the sample is kept moist for a wet hair combing test. After the hair is dried in a constant temperature and humidity chamber, the sample is dried for a dry hair combing test.

[0046] The test results for some embodiments are shown in Table 3, and the test results for some comparative embodiments are shown in Table 4. The meanings of the values ​​in each column are as follows: Baseline: This is the force required to comb hair after using a standard shampoo solution (SDS surfactant solution).

[0047] Sample: The force value required during combing after using the example and comparative sample.

[0048] Residual: This refers to the ratio of the force required to comb hair after using the sample to the force required before using the sample (i.e., sample to baseline). The lower this value, the better the sample improves the hair combing performance. In this column, "ns" indicates no significance, "#" indicates no significance, and "*" or "**" indicates significant significance.

[0049] Improvement rate: This refers to the percentage decrease in the force required to comb hair after using the sample compared to before using the sample. The higher the value, the better the sample improves the hair combing performance, and the smoother and easier the hair is to comb.

[0050] Table 3 Hair combability test of some embodiments

[0051] As can be seen from the combing performance results in Table 3, among the nine examples, Examples 2, 6, 7, and 9 showed significant improvements in both wet and dry hair, while the other five examples only showed significant improvements in dry hair. In other words, the proportion of examples that significantly improved combing performance for both wet and dry hair was 44%.

[0052] Table 4. Hair combability test of partial comparison examples

[0053] As can be seen from the combing performance results in Table 4, among the four comparative examples, Comparative Example 1 showed significant improvement in both wet and dry hair, while the other three comparative examples only showed significant improvement in dry hair. In other words, the proportion of comparative examples that significantly improved combing performance in both wet and dry hair was 25%.

[0054] In summary, considering the overall improvement in combability of wet and dry hair, the shampoo in the example is far superior to the comparative example. The presumed reason is that, in addition to increasing the system viscosity, the lauryl glycoside crosspolymer salt in the example also has complex interactions with other components, thereby affecting the deposition of conditioning ingredients such as silicone emulsion and cationic guar gum on the hair, reducing friction during both wet and dry combing.

[0055] The above-disclosed embodiments are merely preferred embodiments of the present invention and should not be construed as limiting the scope of the present invention. Therefore, any equivalent variations made in accordance with the claims of the present invention are still within the scope of the present invention.

Claims

1. A shampoo containing lauryl glycoside crosspolymer salt, characterized in that, It includes sodium lauryl ether sulfate, cocamidopropyl betaine, and lauryl glycoside crosspolymer salt; the chemical formula of the lauryl glycoside crosspolymer salt is as follows: Where n = 1 to 3, and R is CH3(CH2). 11 - 2. The shampoo containing lauryl glycoside crosspolymer salt as described in claim 1, characterized in that, The mass fraction of the lauryl glycoside crosspolymer salt is 1% to 10%; the purity of the lauryl glycoside crosspolymer salt is 55% to 65%.

3. The shampoo containing lauryl glycoside crosspolymer salt as described in claim 2, characterized in that, The sodium lauryl ether sulfate has a mass fraction of 9.3%–17.8%; the cocamidopropyl betaine has a mass fraction of 5%–8%. The purity of the sodium lauryl ether sulfate is 70%; the purity of the cocamidopropyl betaine is 45%.

4. The shampoo containing lauryl glycoside crosspolymer salt as described in claim 3, characterized in that, The sodium lauryl ether sulfate has a mass fraction of 12.3% to 17.8%; the cocamidopropyl betaine has a mass fraction of 5% to 8%; and the lauryl glycoside crosspolymer salt has a mass fraction of 1% to 7%.

5. The shampoo containing lauryl glycoside crosspolymer salt as described in claim 1, characterized in that, Also includes: Cationic guar gum, silicone emulsion, cocamide MEA, hydrogenated castor oil, ethylene glycol distearate, phenoxyethanol, sodium benzoate, citric acid, sodium chloride, and water.

6. The shampoo containing lauryl glycoside crosspolymer salt as described in claim 5, characterized in that, Components including the following mass fractions: The lauryl glycoside cross-linked polymer salt is 1%–10%. The sodium lauryl ether sulfate content is 9.3%–17.8%. The cocamidopropyl betaine is 5%–8%. The cationic guar gum is 0.2% to 0.5%. The silicone emulsion is 1.5% to 3%. The cocoamide MEA content is 0.8%–10%. The hydrogenated castor oil is 0.2% to 0.3%. The ethylene glycol distearate is 0.8% to 1.0%. The phenoxyethanol content is 0.7% to 0.8%. The sodium benzoate is 0.2% to 0.3%. The citric acid content is 0.04% to 0.1%. The sodium chloride is 1.0%. Water balance.

7. The shampoo containing lauryl glycoside crosspolymer salt as described in claim 6, characterized in that, It also includes decyl glucoside; the mass fraction of said decyl glucoside is 2.5% to 5%; the purity of said decyl glucoside is 55% to 65%.

8. A method for preparing a shampoo containing lauryl glycoside crosspolymer salt as described in claim 5, characterized in that, Includes the following steps: S1. The citric acid, sodium lauryl ether sulfate, cocamidopropyl betaine, and lauryl glycoside crosspolymer salt are added to the water and mixed to obtain intermediate product x; S2. Add the cocoamide MEA, the hydrogenated castor oil, and the ethylene glycol distearate to the intermediate product x, and mix to obtain the intermediate product y; S3. Add the cationic guar gum to the intermediate product y and mix to obtain the intermediate product z; S4. Cool the intermediate product z, add the silicone emulsion, phenoxyethanol, sodium benzoate, and sodium chloride, mix, and obtain the shampoo containing lauryl glycoside crosspolymer salt.

9. The method for preparing the shampoo containing lauryl glycoside crosspolymer salt as described in claim 8, characterized in that, In steps S1, S2, and S3, the mixing method independently includes stirring, and the degree of mixing includes complete dissolution. In step S4, the mixing method includes stirring, and the degree of mixing includes complete dissolution and dispersion. In step S1, the mixing temperature is 80°C; in step S4, the cooling temperature is 48°C.

10. The application of a shampoo containing lauryl glycoside crosspolymer salt as described in any one of claims 1 to 7, characterized in that, Used to increase the viscosity of shampoo.

Citation Information

Patent Citations

  • Cationic polyglyceryl compositions and compounds

    CN103172526A

  • Mild shampoo containing sulfonated alkyl glucoside

    CN103445972A

  • Conditioning shampoo containing cation-modified alkyl polyglycoside

    CN103520021A

  • Mild shampoo and bath bubbles for infants

    CN105943463A

  • Shampoo and preparation method thereof

    CN107982135A